2013
DOI: 10.1186/2193-1801-2-201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of major depressive symptoms among pregnant women by employment status

Abstract: The objectives of our study were to compare the prevalence of major depressive symptoms between subgroups of pregnant women: working women, women who had stopped working, housewives and students; and to identify risk factors for major depressive symptoms during pregnancy. The CES-D scale (Center for Epidemiological Studies Depression scale) was used to measure major depressive symptoms (CES-D score ≥23) in 5337 pregnant women interviewed at 24–26 weeks of pregnancy. Multivariate logistic regression models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
2
27
5
3
Order By: Relevance
“…In contrast to studies in western populations, which mention employment as a strong protective factor against major depression in pregnancy [13], our study found that pregnant women employed outside the home were actually more depressed and anxious than housewives. A study in Karachi, Pakistan also provides opposing results to our findings by concluding that housewives, in general, are more depressed than working women [14].…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to studies in western populations, which mention employment as a strong protective factor against major depression in pregnancy [13], our study found that pregnant women employed outside the home were actually more depressed and anxious than housewives. A study in Karachi, Pakistan also provides opposing results to our findings by concluding that housewives, in general, are more depressed than working women [14].…”
Section: Discussioncontrasting
confidence: 55%
“…An interesting finding in our study was the correlation between the occupation of the pregnant women and antenatal depression and anxiety. In contrast to studies in western population, which mention employment as a strong protective factor against major depression in pregnancy [39], our study found employed pregnant women to be actually more depressed and anxious than housewives. A study in Karachi, Pakistan also apparently contradicts our findings by concluding that housewives, in general, are more depressed than working women [40].…”
Section: Discussioncontrasting
confidence: 99%
“…In a multivariate logistic regression model, several variables were explored including employment, education, social support, socioeconomic status, marital status and smoking [4]. In this study, the Center for Epidemiological Studies Depression (CES-D) scale was used to identify prenatal depression in 5,337 pregnant women at 24–26 weeks gestation.…”
Section: Risk Factorsmentioning
confidence: 99%